2001
DOI: 10.1590/s0036-46652001000400009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of quinidine sensitivity in brazilian Plasmodium falciparum isolates: comparative analysis to quinine and chloroquine

Abstract: Falciparum malaria represents a serious and an increasing world public health problem due to the acquired parasite's resistance to the most available drugs. In some endemic areas, quinidine, a diastereoisomer of the antimalarial quinine, has been employed for replacing the latter. In order to evaluate the use of quinidine as an alternative to the increasing loss of quinine effectiveness in Brazilian P. falciparum strains, as has been observed in the Amazon area, we have assayed quinidine, quinine and chloroqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This was expected since earlier studies conducted in Amazonia suggested that 100% of the P. falciparum isolates circulating in the area were chloroquine-resistant [17]. In addition, most of the “sensitive” isolates had IC50s close to the threshold for sensitivity (100 nM) and therefore represent rather borderline isolates.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This was expected since earlier studies conducted in Amazonia suggested that 100% of the P. falciparum isolates circulating in the area were chloroquine-resistant [17]. In addition, most of the “sensitive” isolates had IC50s close to the threshold for sensitivity (100 nM) and therefore represent rather borderline isolates.…”
Section: Discussionmentioning
confidence: 85%
“…Some isolates showed IC50s very close to the threshold. In any case, this scenario is worrisome because a continuous decreasing in parasite sensitivity has been noted in the Brazilian Amazon [17,21,24-27] and quinine plus doxycycline is actually recommended as P. falciparum second-line treatment by the Brazilian Malaria Control Programme.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, quinine has different effects against Plasmodium and T. gondii. Although quinine shows high activity in in vitro models of Plasmodium (0.272-5.2 μM, and 0.053-8.1 μM determined by (Touré et al, 2008), (Björkman et al, 1991) and (Menezes et al, 2001), no inhibitory effect on T. gondii has been reported (Gomes et al, 2012;Holfels et al, 1994). Against N. caninum, the activity of quinine was moderate (56.6 μM, Table 1 and Figure 1D).…”
Section: Resultsmentioning
confidence: 92%
“…In Brazil, P. falciparum in vitro tests have been performed since 1981 either alone (Ferraroni et al 1981, Reyes 1981, Couto et al 1995, Calvosa et al 2001, Menezes et al 2001, in conjunction with in vivo follow-up studies (Boulos et al 1986, Neifer & Kremsner 1991, Segurado et al 1997, Cerutti et al 1999b or along with molecular genotyping (Póvoa et al 1998, Zalis et al 1998, Vieira et al 2001.…”
mentioning
confidence: 99%